Nondestructive Chemical Analysis of the Iron-Containing Protein Ferritin Using Raman Microspectroscopy. Issue 2 (February 2020) - Hartmann, Carolin; Elsner, Martin; Niessner, Reinhard; Ivleva, Natalia P.
Ferritin is a ubiquitous intracellular iron storage protein of animals, plants, and bacteria. The cavity of this protein acts like a reaction chamber for natural formation and storage of nano-sized particles via biomineralization. Knowledge of the chemical composition and structure of the iron core is highly warranted in the fields of nano technologies as well as biomolecules and medicine. Here, we show that Raman microspectroscopy (RM) is a suitable nondestructive approach for an analysis of proteins containing such nano-sized iron oxides. Our approach addresses: (1) synthesis of suitable reference materials, i.e., ferrihydrite, maghemite and magnetite nanoparticles; (2) optimization of parameters for Raman spectroscopic analysis; (3) comparison of Raman spectra from ferritin with apoferritin and our reference minerals; and (4) validation of Raman analysis by X-ray diffraction and Mössbauer spectroscopy as two independent complementary approaches. Our results reveal that the iron core of natural ferritin is composed of the iron(III) hydroxide ferrihydrite (Fe2 O3 ∙ 0.5 H2 O).